Legal Strategies For Preventing Corruption In The Procurement Of Goods And Services At State-Owned Enterprises - Andi Wahyu Wibisana (Universitas Islam Sultan Agung, 2026)
The procurement of goods and services within state-owned enterprises (SOEs) is the sector in Indonesia with the most widespread and recurring corruption, with state losses due to procurement corruption surging from Rp5.3 trillion between 2016 and 2020 to Rp43.33 trillion between 2021 and 2023. The absence of a decrease in corruption figures despite the ongoing strengthening of anti-corruption regulations indicates a fundamental gap in SOE procurement governance. The core issue is the absence of a comprehensive, integrated, and legally binding prevention strategy. At the same time, SOE boards of directors have the full authority to establish procurement procedures independently without equivalent accountability standards. This study employs a normative-dogmatic legal methodology. The findings reveal that procurement fraud in SOEs occurs systematically across all stages of the procurement cycle and across sectors. Furthermore, it is found that fraud prevention fails due to a ‘trifragmentation’ of the system, which undermines the substance of regulations by containing normative gaps, a supervisory structure co-opted by conflicts of interest, and an internal legal culture that is permissive towards gratification. The discussion concludes that the most coherent academic response is to formulate a single binding legal instrument that closes every fraud loophole at every layer of the procurement cycle, restores the independence of internal oversight, and institutionalises anti-corruption cultural transformation as a corporate obligation.